Financial Management and Development Strategy at Jamiah Syeikh Daud Al-Fathoni (JISDA) South Thailand - Fikree Kabae; Syahrul Amsari (Universitas Negeri Padang, 2025)
Financial management in Islamic educational institutions plays a crucial role in ensuring sustainability and quality improvement. This study examines the financial management strategies implemented at Jamiah Syeikh Daud Al-Fathoni (JISDA), focusing on optimizing financial sources such as zakat, infaq, sadaqah, and waqf. The research employs a qualitative descriptive method, using literature reviews, interviews, and institutional financial reports to analyze Jamiah Syeikh Daud Al-Fathoni (JISDA) financial strategies. The findings reveal that Jamiah Syeikh Daud Al-Fathoni (JISDA) integrates waqf-based productive assets, establishes a sharia cooperative, and utilizes digital financial systems to enhance financial transparency and efficiency. Furthermore, collaboration with Islamic financial institutions and the development of crowdfunding platforms significantly contributes to institutional sustainability. The results indicate that implementing Islamic financial principles strengthens Jamiah Syeikh Daud Al-Fathoni (JISDA) financial resilience, ensuring operational stability and institutional growth. The study concludes that an innovative and adaptive financial management model incorporating digitalization and community-based fundraising is essential for Islamic higher education institutions. Future research should explore the effectiveness of fintech-based financial solutions in enhancing financial independence in Islamic educational institutions